PENGEMBANGAN BAHAN AJAR DIGITAL PADA MATA PELAJARAN IPAS KELAS IV DI MI/SD - Sulistyowati, Sulistyowati; Mahmudah, Istiyati; Syabrina, Muhammad; Syar, Nur Inayah; Rahmad, Rahmad; Wahid, Abdul (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2024)
In the era of industrial revolution 4.0, teaching materials need to be adapted to technological developments so that students can be interested. The type of teaching material that can attract students' interest is teaching material in the form of interactive media. This research aims to develop digital teaching materials in the form of interactive learning media that can be used by students in class IV in learning science and technology. This research follows the ADDIE model with five stages, namely analysis, design, development, implementation, and evaluation. Data was collected through interviews, observation, documentation and questionnaires. The results of questionnaires from media, material experts and field trials show that this interactive learning media is very suitable, with a percentage score reaching 95% including